A new route for the synthesis of 1-deazaguanine and 1-deazahypoxanthine - Bereiter, Raphael; Oberlechner, Marco; Micura, Ronald (Beilstein Journal of Organic Chemistry, 2022)
Imidazopyridines and pyrrolopyrimidines are an important class of compounds in medicinal chemistry. They can also be considered as deaza-modified purine nucleobases, and as such have attracted a lot of interest recently in the context of RNA atomic mutagenesis. In particular, for 1-deazaguanine (c1G base), a significant increase in demand is apparent. Synthetic access is challenging and the few reports found in the literature suffer from the requirement of hazardous intermediates and harsh reaction conditions. Here, we report a new six-step synthesis for c1G base, starting from 6-iodo-1-deazapurine. The key transformations are copper catalyzed C–O-bond formation followed by site-specific nitration. A further strength of our route is divergency, additionally enabling the synthesis of 1-deazahypoxanthine (c1I base).
Keywords: deazapurine; heterocycles; imidazopyridines; nucleoside; nucleotides; pyrrolopyrimidines; RNA atomic mutagenesis

(untitled) - Vanda, D.; Zajdel, P.; Soural, M. (Eur. J. Med. Chem., 2019)

(untitled) - Azam, M. A.; Thathan, J.; Jubie, S. (Bioorg. Chem., 2015)

(untitled) - De Coen, L. M.; Heugebaert, T. S. A.; García, D.; Stevens, C. V. (Chem. Rev., 2016)

(untitled) - Revankar, G. R.; Gupta, P. K.; Adams, A. D.; Dalley, N. K.; McKernan, P. A.; Cook, P. D.; Canonico, P. G.; Robins, R. K. (J. Med. Chem., 1984)

(untitled) - Scott, R.; Karki, M.; Reisenauer, M. R.; Rodrigues, R.; Dasari, R.; Smith, W. R.; Pelly, S. C.; van Otterlo, W. A. L.; Shuster, C. B.; Rogelj, S.; Magedov, I. V.; Frolova, L. V.; et al. (ChemMedChem, 2014)

(untitled) - Gibson, C. L.; La Rosa, S.; Ohta, K.; Boyle, P. H.; Leurquin, F.; Lemaçon, A.; Suckling, C. J. (Tetrahedron, 2004)

(untitled) - Kaiser, M. M.; Baszczyňski, O.; Hocková, D.; Poštová-Slavětínská, L.; Dračínský, M.; Keough, D. T.; Guddat, L. W.; Janeba, Z. (ChemMedChem, 2017)

(untitled) - Montgomery, J. A.; Niwas, S.; Rose, J. D.; Secrist, J. A., III; Babu, Y. S.; Bugg, C. E.; Erion, M. D.; Guida, W. C.; Ealick, S. E. (J. Med. Chem., 1993)

(untitled) - Stipković Babić, M.; Makuc, D.; Plavec, J.; Martinović, T.; Kraljević Pavelić, S.; Pavelić, K.; Snoeck, R.; Andrei, G.; Schols, D.; Wittine, K.; Mintas, M. (Eur. J. Med. Chem., 2015)

(untitled) - Chang, L. C. W.; von Frijtag Drabbe Künzel, J. K.; Mulder-Krieger, T.; Westerhout, J.; Spangenberg, T.; Brussee, J.; IJzerman, A. P. (J. Med. Chem., 2007)

(untitled) - Cristalli, G.; Vittori, S.; Eleuteri, A.; Grifantini, M.; Volpini, R.; Lupidi, G.; Capolongo, L.; Pesenti, E. (J. Med. Chem., 1991)

(untitled) - Iaroshenko, V. O.; Ostrovskyi, D.; Petrosyan, A.; Mkrtchyan, S.; Villinger, A.; Langer, P. (J. Org. Chem., 2011)

(untitled) - Neuner, S.; Falschlunger, C.; Fuchs, E.; Himmelstoss, M.; Ren, A.; Patel, D. J.; Micura, R. (Angew. Chem., Int. Ed., 2017)

(untitled) - Polacek, N. (Chimia, 2013)

(untitled) - Seela, F.; Debelak, H.; Usman, N.; Burgin, A.; Beigelman, L. (Nucleic Acids Res., 1998)

(untitled) - Bereiter, R.; Renard, E.; Breuker, K.; Kreutz, C.; Ennifar, E.; Micura, R. (J. Am. Chem. Soc., 2022)

(untitled) - Egger, M.; Bereiter, R.; Mair, S.; Micura, R. (Angew. Chem., Int. Ed., 2022)

(untitled) - Markees, D. G.; Kidder, G. W. (J. Am. Chem. Soc., 1956)

(untitled) - Gorton, B. S.; Shive, W. (J. Am. Chem. Soc., 1957)

(untitled) - Schelling, J. E.; Salemink, C. A. (Recl. Trav. Chim. Pays-Bas, 1974)

(untitled) - Temple, C., Jr; Smith, B. H.; Kussner, C. L.; Montgomery, J. A. (J. Org. Chem., 1976)

(untitled) - Wolter, M.; Nordmann, G.; Job, G. E.; Buchwald, S. L. (Org. Lett., 2002)

(untitled) - Deghati, P. Y. F.; Wanner, M. J.; Koomen, G.-J. (Tetrahedron Lett., 2000)

(untitled) - Deghati, P. Y. F.; Bieräugel, H.; Wanner, M. J.; Koomen, G.-J. (Tetrahedron Lett., 2000)

(untitled) - Wanner, M. J.; Rodenko, B.; Koch, M.; Koomen, G. J. (Nucleosides, Nucleotides Nucleic Acids, 2004)

(untitled) - Orlandi, M.; Tosi, F.; Bonsignore, M.; Benaglia, M. (Org. Lett., 2015)

(untitled) - Xiao, Y.; Xu, Y.; Cheon, H.-S.; Chae, J. (J. Org. Chem., 2013)

(untitled) - Lembacher-Fadum, C.; Gissing, S.; Pour, G.; Breinbauer, R. (Monatsh. Chem., 2021)

(untitled) - Hirao, Y.; Seo, S.; Kubo, T. (J. Phys. Chem. C, 2019)